NUBPL mitochondrial disease: new patients and review of the genetic and clinical spectrum. Issue 5 (9th June 2020) - Kimonis, Virginia; al Dubaisi, Rehab; Maclean, Andrew E; Hall, Kathy; Weiss, Lan; Stover, Alexander E; Schwartz, Philip H; Berg, Bethany; Cheng, Cheng; Parikh, Sumit; Conner, Blair R; Wu, Sitao; et al.
Abstract : Background: The nucleotide binding protein-like ( NUBPL ) gene was first reported as a cause of mitochondrial complex I deficiency (MIM 613621, 618242) in 2010. To date, only eight patients have been reported with this mitochondrial disorder. Five other patients were recently reported to have NUBPL disease but their clinical picture was different from the first eight patients. Here, we report clinical and genetic findings in five additional patients (four families). Methods: Whole exome sequencing was used to identify patients with compound heterozygous NUBPL variants. Functional studies included RNA-Seq transcript analyses, missense variant biochemical analyses in a yeast model ( Yarrowia lipolytica ) and mitochondrial respiration experiments on patient fibroblasts. Results: The previously reported c.815-27T>C branch-site mutation was found in all four families. In prior patients, c.166G>A [p.G56R] was always found in cis with c.815-27T>C, but only two of four families had both variants. The second variant found in trans with c.815-27T>C in each family was: c.311T>C [p.L104P] in three patients, c.693+1G>A in one patient and c.545T>C [p.V182A] in one patient. Complex I function in the yeast model was impacted by p.L104P but not p.V182A. Clinical features include onset of neurological symptoms at 3–18 months, global developmental delay, cerebellar dysfunction (including ataxia, dysarthria, nystagmus and tremor) and spasticity. Brain MRI showed cerebellar atrophy. Mitochondrial function studies on patient fibroblasts showed significantly reduced spare respiratory capacity. Conclusion: We report on five new patients with NUBPL disease, adding to the number and phenotypic variability of patients diagnosed worldwide, and review prior reported patients with pathogenic NUBPL variants.